Thunderstorm and fixation of Nitrogen in rain (MAUSAM, 1955)
Recent determinations  of the nitrates and ammonia in rain water in Sweden has led to the conclusion  that thunder, i.e., electrical spark discharges in the atmosphere, is not the determining factor in  the production  of  Nitrogen compounds formed in rain water. In the light of the above conclusion, available  data of  combined  Nitrogen in rain water in India have  been examined. It supports  the conclusions reached by Swedish workers.